Transgression: Afghan Refugee Women as - Tasleem Malik; Faizullah Jan (SAGE Open)
This paper argues that as part of a discursive strategy to securitize Afghan refugees in Pakistan, their womenfolk were labeled as gelumjum (a euphemism for prostitutes). Problematizing the othering of women refugees as transgressors, we discuss the structures and material conditions that forced Afghan women into prostitution as a livelihood strategy in the absence of societal cushion. It also discusses gelumjum as a problematized identity, a transgressor of the borders of the State, bodily borders, and borders of morality. As a refugee, gelumjum is an anomaly to the global political order defined by sovereignty, borders, and citizenship. They are also considered transgressors of the moral order, the law of home and marriage, and the customs of traditional society. Lastly, as transgressors of the bodily borders, gelumjum is also constructed as a pathological danger to public health. The study posits how this discursive strategy became a technology of control/power that created the norm/prohibition via the transgressive body, a normalized masculine public space. It demarcated the inside/outside boundaries of acceptable gendered behavior. This study is first of its nature as there is no prior research/scholarly endeavor in this domain. Gelumjum remained an overlooked phenomenon in the works on Afghan refugees, which reflects the differential representation on the basis of gender and deviance from the accepted norms. Hence, this study contributes to the scarce literature on Afghan women, particularly Afghan sex workers in host communities.